The epidemiology of overfeeding in mechanically ventilated intensive care patients. (April 2020) - Tanaka, Aiko; Hamilton, Kate; Eastwood, Glenn M.; Jones, Daryl; Bellomo, Rinaldo
Summary: Background and aims: Nutrition research in the Intensive Care Unit (ICU) typically focusses on the epidemiology of underfeeding, particularly early in the ICU admission. Once the acute phase of critical illness has resolved, patients may be at risk of overfeeding. We assessed for the frequency and consequences of potential overfeeding in ICU patients mechanically ventilated (MV) for at least 10 days. Methods: Retrospective analysis of 105 MV patients including caloric input, estimated caloric requirements using the Schofield equation, and association between caloric input and several pre-defined clinical outcomes. To increase likelihood of detecting overfeeding, we conducted a post-hoc sensitivity analysis for sub-groups of patients who received on average < 25 kcal/kg/day (N = 55) and >30 kcal/kg/day (N = 17) between day 7–10 and performed repeat ANOVA. Results: There were no differences in the pre-defined outcomes for those given over, and below 25 kcal/kg/day. On each study day, approximately 25% of patients received >30 kcal/kg/day. Higher caloric delivery was statistically associated with increased minute ventilation on each study day (Spearman Rho approx 0.27;p ≤ 0.007) and also in sub-group analysis (p< 0.001). Higher caloric delivery was also associated with more frequent diarrhoea (p= 0.02) and greater insulin requirement. However, these differences did not translate into increased duration of mechanical ventilation, length of stay, or increased mortality. Higher caloric intake was less strongly associated with serum urea and creatinine, but not associated with agitation, abnormal liver function tests, fever, or antibiotic prescription. Conclusions: Delivery of more than 25 kcal/kg/day was not associated with adverse outcomes. On post-hoc analysis, delivery of more than 30 kcal/kg/day was associated with increased minute ventilation, diarrhoea and insulin requirements but no differences in length of ventilation or in-hospital mortality.